2002
DOI: 10.1079/joh2002116
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo studies on the bioactivity of a ginger (Zingiber officinale) extract towards adult schistosomes and their egg production

Abstract: The bioactivity of an ethyl acetate extract of ginger (Zingiber officinale) towards Schistosoma mansoni adult pairs, both cultured in vitro and in vivo in laboratory mice, was investigated by monitoring worm mortality and fecundity. In vitro, a concentration of 200 mg l(-1) of extract killed almost all worms within 24 h. Male worms seemed more susceptible than female under these conditions. Cumulative egg output of surviving worm pairs in vitro was considerably reduced when exposed to the extract. For example,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
61
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 35 publications
9
61
1
4
Order By: Relevance
“…For example, curcumin, extracted from the rhizome of Curcuma longa [37], some phloroglucinol derivatives obtained from the rhizomes of Dryopteris species [38], and artenusate [36] presented in vitro inhibitory effects on schistosome oviposition. A decrease of the egg output of schistosomes was also observed for Nigella sativa crushed seeds (black seeds) [39] and an extract of ginger rhizomes (Zingiber officinale) [33]. Our data corroborate these in vitro studies and showed that DS 01 is toxic at higher doses, while at sub-lethal doses, it significantly interferes with the reproductive fitness of S. mansoni.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…For example, curcumin, extracted from the rhizome of Curcuma longa [37], some phloroglucinol derivatives obtained from the rhizomes of Dryopteris species [38], and artenusate [36] presented in vitro inhibitory effects on schistosome oviposition. A decrease of the egg output of schistosomes was also observed for Nigella sativa crushed seeds (black seeds) [39] and an extract of ginger rhizomes (Zingiber officinale) [33]. Our data corroborate these in vitro studies and showed that DS 01 is toxic at higher doses, while at sub-lethal doses, it significantly interferes with the reproductive fitness of S. mansoni.…”
supporting
confidence: 86%
“…In contrast, disparities in drug susceptibility between males and females have been previously reported in some in vitro activity trials. Male worms of S. mansoni have been found to be more susceptible than female worms in praziquantel resistance studies [5] [32] and studies on the bioactivity of a ginger extract [33]. On the other hand, studies with compounds such as (aminoalkane)thiosulfuric acids [34], 2-(butylamino)-1-phenyl-1-ethanethiosulfuric acid [35], and artenusate [36] showed higher survival rates for males than females.…”
mentioning
confidence: 99%
“…Although a numerical decrease (7.26-17.71%) in total number of worms was recorded (Table 4), yet no statistically significant changes were recorded in the total number of worms, tissue egg load and % egg developmental stages after the oral administration of plant extracts. Concerning Z. officinale, results are in agreement with those of Sanderson et al (2002) who reported that neither oral nor subcutaneous administration of 150 mg/ kg of ethyl acetate extract of ginger produced any significant reduction in S. mansoni worm numbers compared with untreated controls. Conversely, Mostafa et al (2011) reported that worm burden and the egg density in liver and faeces of mice treated with ginger were fewer than in non-treated ones.…”
Section: Safety and In Vivo Efficacy Against S Mansonisupporting
confidence: 91%
“…A 90-100% mortality of Schistosoma worms was found affected in vitro by 4 mg=mL goyazensolide, a component extracted from Eremanthus goyazensis (Barth et al, 1997), and 200 mg l À1 of an ethyl acetate extract of ginger, Zingiber officinale (Sanderson et al, 2002). In vitro antischistosomal activity was possessed by robustic acid and an isoflavone compound isolated from the seeds of the tree Millettia thonningii (Lyddiard et al, 2002), as well as extracts of Scilla natalensis and Ledebouria ovatifolia (Sparg et al, 2002).…”
Section: Resultsmentioning
confidence: 99%